Hospitalized dogs recovery from naturally occurring heatstroke; does serum heat shock protein 72 can provide prognostic biomarker? - Bruchim, Yaron (Cell Stress Chaperones, 2015)
Heatstroke is a serious illness in dogs characterized by core temperatures above 41 °C with central nervous system dysfunction. Experimental heatstroke models have tried to correlate biomarker levels with the severity of the syndrome. Serum heat shock protein (eHSP70) levels were recently evaluated as a biomarker of heat tolerance and acclimation, their role as a marker of heatstroke is inconclusive. Here, we monitored eHSP70 levels in correlation with systemic biomarkers in 30 naturally occurring canine heatstroke cases. Thirty dogs diagnosed with environmental (33 %) or exertional (66 %) heatstroke admitted to hospital (0–14 h post-injury) were tested for biomarkers of organ damage and coagulation parameters. eHSP70 levels were measured upon admission and 4, 12, and 24 h later (T1, T2, and T3, respectively). No differences were found between exertional and environmental heatstroke cases. The eHSP profile demonstrated an inverted bell shape, with the lowest levels at the 12 h time point. A positive correlation between eHSP70, lactate, and aPPT was also noted at T2 in all the dogs in the study. Twenty-four h after presentation, eHSP70 levels returned to those measured upon admission, this change was only significant in the survivors. The obtained results suggest that eHSP72 level profile may be predictive of survival.